Seepage Detection Using Passive Temperature Measurements by Fiber Optic DTS (Informatica, 2024)
This article is an extended abstract of the doctoral dissertation “Optimization of early seepage detection in embankments using a distributed temperature system based on fiber optic sensing” [1]. Distributed Temperature Sensors (DTS) measure temperature precisely with high spatial resolution, enabling seepage flow detection through the interpretation of temperature measurement. Active DTS measurement which introduces heat into the soil to monitor its dissipation, has been extensively studied for seepage detection. However, the potential of passive measurement, which measures natural soil temperature, for seepage detection demands further exploration. The doctoral research investigated the capability of passive DTS measurements for seepage detection. The findings show that passive DTS detects very small temperature variations as a result of the seepage flow. Additionally, the results offer valuable insights into the coupled hydro-thermal behavior and the influence of seepage on heat transfer. The thesis classified and compared different techniques for temperature data calibration and interpretation. Furthermore, an interpretation approach based on numerical simulation and a fully dynamic calibration technique were developed.